Anatomical Evaluation of a Cortical Button for Distal Biceps Tendon Repairs. (June 2013) - Duncan, Douglas; Lancaster, Gerard; Marsh, Stephanie G.; Michaelson, Jefferey E.; Lemos, Stephen E.
Background: The posterior interosseous nerve (PIN) is at risk for injury during one-incision distal biceps tendon repair using a cortical button. The purpose of this study was to evaluate the proximity of a cortical button to the PIN during one-incision repairs of the distal biceps tendon using human cadaveric models. Method: In ten cadaveric elbows the biceps tendon was identified, traced to its insertion, and transected. With the forearm supinated, a guide pin was drilled through the radial tuberosity at a 0°, perpendicular to the table. A dorsal incision was used to identify the PIN. The tendon was repaired with a cortical button, ensuring the device lay in line with the radial shaft. The distance from the device to the PIN was measured using digital calipers. This process was repeated with the guide pin aimed at 20° proximal toward the radiocapitellar joint (RCJ) and 30° distal toward the wrist. The data were compared using a Student's paired t -test. Results: The average distance from the device to the PIN with the straight posterior insertion was 8.94 mm, 11.86 mm with 20° proximal, and 0.55 mm with 30° distal angles. The distance between the button and the PIN was significantly greater when aiming the device 20° toward the RCJ compared to the straight insertion technique ( p =0.0061). Conclusions: The distance between the PIN and cortical button can be significantly increased by aiming the guide pin between 0° and 20° proximal toward the RCJ and placing the device in line with the radial shaft.